The Workers: An Experiment in Reality. The West - Wyckoff, Walter A. (Walter Augustus), 1865-1908 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Workers: An Experiment in Reality" by Walter A. Wyckoff is a social commentary written in the late 19th century. The work explores the struggles of the unemployed in urban America, focusing on their desperate search for work amidst the backdrop of a burgeoning industrial society. The narrative is driven by the experiences of Tom Clark and the author himself, who navigate the harsh realities of life on the fringes of society as they seek employment and survival. At the start of the narrative, the author describes his arrival in Chicago and the chilling reality faced by those without work. He recounts his experiences with his companion Tom Clark as they confront hunger, cold, and despair within the congested labor market. The two men, initially hopeful for job opportunities, find themselves sleeping in a station-house after a long day of searching for work. They share moments of camaraderie born from their mutual struggle, while also reflecting on the broader societal issues that lead individuals like them to feel superfluous in the vast machinery of the city. As they wait for a chance to escape their dire circumstances, the narrative sets a poignant tone that reflects the broader themes of dignity, hope, and survival against the odds. (This is an automatically generated summary.)
The army of the unemployed -- Living by odd jobs -- Finding steady work -- A hand-truckman in a factory -- Among the revolutionaries -- A road builder on the World's Fair Grounds -- From Chicago to Denver -- From Denver to the Pacific.
Release date is 2021-02-08
Mike Stember and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Working class -- United States; Unemployed -- United States